2017
DOI: 10.1007/s11356-017-9121-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fine particulate matter and its constituents on emergency room visits for asthma in southern Taiwan during 2008–2010: a population-based study

Abstract: This population-based study evaluated the short-term association between fine particulate matter (PM) concentrations and its constituents and hospital emergency room visits (ERVs) for asthma in southern Taiwan during the period 2008-2010. Data on hospital ERVs for asthma and ambient PM levels and its constituents were obtained from the National Health Insurance Research database and the Environmental Protection Administration, respectively. The quasi-Poisson generalized additive model was used to explore the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
1
20
1
5
Order By: Relevance
“… 8 Many epidemiological studies worldwide have addressed the correlation between the concentrations of PM and hospital visits due to respiratory diseases ( Table 1 ). 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Pm As a Risk Factor To Public Healthmentioning
confidence: 99%
“… 8 Many epidemiological studies worldwide have addressed the correlation between the concentrations of PM and hospital visits due to respiratory diseases ( Table 1 ). 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 …”
Section: Pm As a Risk Factor To Public Healthmentioning
confidence: 99%
“…Currently, it is a well‐known air pollutant threatening public health. Clinical studies reported that long‐term exposure to the particles associated with reduction in pulmonary function, exacerbation of chronic respiratory diseases such as asthma and chronic obstructive pulmonary disease (COPD), and increased incidence and mortality of lung cancer . Epidemiological studies revealed an inverse relationship between the particles inhalation and human average life span .…”
Section: Introductionmentioning
confidence: 99%
“…[1] due to its chronic adverse human health effects [2]. Some previous studies [3,4] have revealed that PM 2.5 constituents such as sulfate, nitrate, and ammonium were responsible for these effects. Sulfate (SO 4 2− ), nitrate (NO 3 − ), and ammonium (NH 4 + ) are the major water-soluble inorganic (WSI) species, which represent very large fractions in PM 2.5 depending on source emissions, human activities, chemical reactions, and meteorological conditions [5].…”
Section: Introductionmentioning
confidence: 99%